The effect of fraud diamond and financial stability on fraudulent financial statement with anti fraud as a moderating variable - Sutisna, Ujang; Yazid, Helmi; Lestari, Tri (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The purpose of this study was to determine the effect of fraud diamond and financial stability on fraudulent financial statement with anti-fraud as a moderating variables in banking companies listed on the Indonesia stock exchange 2016-2020. The sample used in this study is 28 companies. The data used is secondary data. The data analysis technique used is quantitative. Structural Equation Modeling is used as an analysis with the help of Smart SPSS software version 25. The results in this study indicate that pressure has no effect on fraudulent financial statements, opportunity has no effect on fraudulent financial statements, rationalization has effect on fraudulent financial statements, ability has no effect on fraudulent financial statements, financial stability has effect on fraudulent financial statements, anti-fraud has not moderate the relationship between pressure on fraudulent financial statements, Anti- fraud has not moderate the relationship between opportunity and fraudulent financial statements, Anti-fraud moderates the relationship between rationalization and fraudulent financial statements, Anti-fraud does not moderate the relationship between ability and fraudulent financial statements, Anti-fraud moderates the relationship between financial stability and fraudulent financial statements.